Effect Of Multi-Elemental Doping On The Catalytic Activity Of Carbocatalysts For Antibiotics Degradation Via Peroxymonosulfate Activation - Gasim, Mohamed Faisal Malik (2024)
Presently, the utilization of heteroatoms- and/or metal-doped carbocatalysts for the degradation of organic pollutants via catalytic peroxymonosulfate (PMS) activation has drawn significant attention. Yet, there exists a necessity for an in-depth exploration in: (i) understanding the influence of carbonaceous properties on N, S-co-doping, (ii) assessing the effectiveness of heteroatoms tri-doping and apprehending the intra-actions among multiple heteroatoms, and (iii) identifying new transition metals that are suitable for co-doping with N to improve the catalytic activity of carbocatalysts. In view of these research gaps, the main objective of this study is to prepare multi-doped carbocatalysts for PMS activation and unveil the roles of the doped elements in the catalytic activity. Firstly, five N, S-co-doped carbocatalysts were prepared from different carbonaceous precursors, namely sawdust (SD), biochar (BC), carbon-nanotubes (CNTs), graphite (GP), and graphene oxide (GO) and compared. Generally, as the graphitization degree increased, the extent of N and S doping decreased, graphitic N configuration is preferred, and S configuration is unaltered. NS-CNTs illustrated the highest catalytic removal of ciprofloxacin (CIP) under PMS activation (0.037 min−1) due to its remarkable conductivity (3.38 S m−1) and defective sites (ID/IG = 1.28). The PMS activation pathway was dominated by singlet oxygen generation and electron-transfer regime. Secondly, N, S, B-tri-doped biochar was fabricated via a one-pot calcination technique.